HUBUNGAN BERAT ISI DAN KUAT TARIK BETON SERAT BAMBU DENGAN ABU CANGKANG LOKAN DAN ABU SEKAM PADI - Elhusna Elhusna; Agustin Gunawan; Reizki Darmawan (Universitas Bengkulu, 2019)
Concrete which has significant weight is good at compressive strength and poor at tensile strength. This study aimed to find out the relationship between the tensile strength and density of bamboo fiber concrete which 40 % of the fine aggregate was replaced with the sea shell ash (ACL) and the rice husk ash (ASP). The bamboo fiber variations which used, 0,25 % (V1) dan 0,50 % (V2) were calculated from the cement weight. Each fiber bamboo variations has 3samples of ACL and ASP weight ratio e.g 35:65 (C1), 50:50 (C2), 65:35 (C3). 3 concrete cylinders of diameter 15 cm and height 30 cm were made for each samples. All the specimens were compared to the normal concrete of water cement ratio 0,45 and slump value 6-10 cm.The specimens were made and maintained by SK SNI T-15-1990-03 and SNI 03-2493-1991. The tensile strength of the specimens were tested at the age of 28 days according to SNI 03-24912002. The highest tensile strength was belonged to V2C2. The significance density (2.347,57 kg/m3) belong to the normal concrete. The highest of the density and the tensile strength of eachvariation of ACL and ASP were occurred at the bamboo fiber concrete 0,5 % (V2).